P-504 Quality of life and Sexual Dysfunction in Bologna poor ovarian responders (POR). (30th June 2022) - Hernandez Hernandez, M; García, S; Martínez, F; Polyzos, N.P
Abstract: Study question: Is quality of life (QoL) and sexual function of poor ovarian responders affected by patients' age and ovarian reserve? Summary answer: QoL and sexual function in POR are only affected by infertility duration and number of previous IVF attempts; not by patients' age and ovarian reserve. What is known already: Diagnosis of infertility is a common cause of sexual health disorders. Couples undergoing Assisted Reproductive Technology (ART) can face emotional stress and feelings of inadequacy or guilt that may interfere in their quality life and sexual function, Poor ovarian responders may represent a group of patients with compromised sexual function and quality of life, owing to either their advanced age or the decline in the serum androgen levels observed in this population. Nonetheless, up to date evidence is scarce concerning clinical factors that may affect quality of life and sexual function of women with poor ovarian response. Study design, size, duration: In a prospective study conducted between 2015 and 2021 we collected questionnaires from poor ovarian responders fulfilling the Bologna criteria concerning their quality of life and sexual function. Participants/materials, setting, methods: Overall 70 women undergoing IVF treatment who fulfilled Bologna's criteria for poor ovarian responders were interviewed at their first visit. Sexual distress was evaluated using the Female Sexual Distress Scale-Revised (FSDSR) and Quality of life was measured by a fertility questionnaire (FertiQOL). Bivariate statistical analysis was conducted in order to evaluate clinical factors (patients' age, duration of infertility, previous IVF attempts and ovarian reserve) that could potentially negatively affect sexual distress and quality of life. Main results and the role of chance: Patients' mean age was 38.6 years old (with 20.6% of the patients being under 35, 33.8% between 35-39 and 45.6% were above 40 years). Infertility duration was less than a year for 22.1% of patients and over one year for 77.9% of patients. Most of patients (80.9%) had at least one previous IVF/ICSI treatment. Quality of life and sexual function, as defined by FertiQol and FSDS-R scores, were comparable among different age groups, and older patients had similar QoL and sexual function with younger patients. Similarly, ovarian reserve did not affect any of the primary outcomes and no association has been found with AFC and FertiQol and FSDS-R scores. The only variables affecting FertiQol and FSDS-R scores were the duration of infertility and the number of previous IVF attempts. Quality of life was significantly lower (75.4 vs 85.9, p < 0.001) among poor responders with previous IVF attempts (> or = 1), whereas sexual distress was higher (10.6 vs 2.54, p < 0.001) in women with previous IVF/ICSI treatment (>0 or = 1) and women with longer duration of infertility (>1 year vs ≤ 1 year) (10.2 vs 4.9, p = 0.049). Limitations, reasons for caution: The results are only applicable to women who fulfil the Bologna criteria for poor ovarian response and cannot be generalized to all infertile women. Wider implications of the findings: Low ovarian reserve and patients' age have limited effect on quality of life and sexual distress of poor ovarian responders. Social and sexual concerns should be taken in consideration in Bologna poor responders, especially in those with longer duration of infertility and previous failed IVF attempts independent of their age. Trial registration number: Not applicable